Comparing mortality rates on CAPD/CCPD and hemodialysis. The Canadian experience: fact or fiction? - Schaubel, DE; Morrison, HI; Fenton, SS (Peritoneal dialysis international, 1998)
To compare mortality rates on hemodialysis (HD) to rates on continuous ambulatory/cyclic peritoneal dialysis (CAPD/CCPD), to contrast our results with those of other recent investigations, and to discuss reasons for discrepancies. Patient-specific data obtained from the Canadian Organ Replacement Register on patients initiating renal replacement therapy (RRT) between 1 January 1990 and 31 December 1995 (n = 14 483). Recent mortality comparisons of CAPD and HD. Mortality rate ratio (RR) based on "as-treated" (AT) analysis incorporating treatment modality switches and adjusting for age, primary renal diagnosis, and comorbid conditions using Poisson regression. Hazard ratios (HR) were estimated using Cox regression and based on an "intent-to-treat" (ITT) analysis wherein patients were classified based on dialytic modality received on follow-up day 90. Adjusted mortality rates were significantly decreased on CAPD/CCPD relative to HD [RR = 0.73, 95% confidence interval (CI) = (0.69, 0.77)] based on the AT analysis. Most of the protective effect of CAPD/CCPD was concentrated in the first 2 years of follow-up post-RRT initiation. Based on the ITT analysis, the estimated CAPD/ CCPD effect was greatly reduced, with HR = 0.93 (0.87, 0.99). We provide further evidence that CAPD/CCPD is not an inferior dialytic modality to HD, particularly in the short term. Comparing mortality rates on CAPD/CCPD and HD is inherently difficult due to the potential for bias. Discrepancies between our results and those of previous investigations, and variability in findings among previous studies, relate to differences in clinical and demographic setting, patient populations, study design, statistical methods, and interaction between the dialytic modality effect and various other covariables.